(untitled) - Atkins, E. Taylor (Durham, 2001)
Blue Nippon emerges from the author's mastery of jazz as a cultural medium, an in-depth knowledge of the scholarship on jazz as an intercultural and historical phenomenon, and from a concern to use cultural theory to come to terms with the specificity of the Japanese history of jazz.
Keywords: Jazz; History and criticism; Japan